ANALISIS KELAYAKAN FINANSIAL USAHATANI TERUBUK (Saccharum Edule Hassk) DI DESA CINTALAKSANA KECAMATAN TEGALWARU KABUPATEN KARAWANG - Pebrin, Triana; Sulandjari, Kuswarini; Yusiana, Ekalia (Universitas Galuh, 2023)
Terubuk is an indigenous vegetable or local vegetable from Karawang Regency. The purpose of this study, to analyze financial feasibility of farm income terubuk in the village of Cintalaksana Tegalwaru District, Karawang regency. This research is a quantitative descriptive analytical research. Sampling using saturated sample method, as many as 20 farmers. Data in the form of primary and secondary data, taken through interviews and observation with the help of a questionnaire. Data were analyzed using total cost analysis, revenue, revenue, R/C ratio, and Break Even Point. The results of the study concluded, on average the total was Rp5.930.286/ha/MT, revenue was Rp9.663.571/ha/MT, income was Rp3.733.286/ha/MT. The R/C ratio is 1,6, meaning that the terubuk farming is feasible to be cultivated with the BEP. The production of terubuk farming is 1,738 stems/ha/MT. farming is profitable because the total production more than the production BEP is 7,236 stems/ha/MT BEP The price of the terubuk farming was Rp819/culm, terubuk farming was stated to be profitable because the terubuk price was more than the BEP price, which was Rp1.300/cub.